1998
DOI: 10.1183/09031936.98.12020380
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cells and mediators in bronchial lavage of patients with chronic obstructive pulmonary disease

Abstract: Cigarette smoking is the main cause of chronic obstructive pulmonary disease (COPD) [1][2][3]. The pathogenesis of smoke-induced COPD has been evaluated in a number of studies showing the accumulation of inflammatory cells in patients' airways: predominantly polymorphonuclear leukocytes in samples representative of intraluminal infla-mmation (sputum, bronchial and bronchoalveolar lavage) and mainly mononuclear cells, lymphocytes and macrophages, in tissue specimens [4][5][6][7][8][9][10][11][12][13].While the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
196
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(215 citation statements)
references
References 27 publications
11
196
1
7
Order By: Relevance
“…Significantly enhanced IL-8 levels were found in C. pneumoniaeinfected and unstimulated AMs from COPD patients in the present study. Increased sputum levels of IL-8 associated with enhanced neutrophil activation have been previously reported during acute exacerbation in COPD patients [27,28]. The precise role of exacerbations in patients suffering from chronic obstructive lung disease in tissue destruction and FEV1 decline is still the subject of controversy.…”
Section: Discussionmentioning
confidence: 98%
“…Significantly enhanced IL-8 levels were found in C. pneumoniaeinfected and unstimulated AMs from COPD patients in the present study. Increased sputum levels of IL-8 associated with enhanced neutrophil activation have been previously reported during acute exacerbation in COPD patients [27,28]. The precise role of exacerbations in patients suffering from chronic obstructive lung disease in tissue destruction and FEV1 decline is still the subject of controversy.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical investigations have reported that eosinophils are increased in the sputum and bronchial biopsies of patients with AECOPD (31,32). Increased levels of ECP in serum (24,33), bronchoalveolar lavage fluid (34) and induced sputum (35) have been observed in patients with AECOPD. Hospers et al (20) proposed that peripheral blood eosinophilia may also lead to a higher mortality rate for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher numbers of neutrophils, macrophages and CD8 positive T-cells in the peripheral airways of COPD patients were found as compared to smokers [10,[17][18][19], whereas others did not [10,19,20]. Two studies showed a higher percentage of neutrophils and higher IL-8 levels in broncho-alveolar lavage of COPD patients [13,21], whereas Linden et al found no differences [7]. A few studies showed higher numbers of neutrophils [22], CD3, CD4 [23] CD8 positive T-cells [23,24] in bronchial biopsies, whereas other studies found no differences in neutrophils [24], CD3, CD4 [22,24] and CD8 positive T-cels [22], macrophages, eosinophils and mast cells [22,24].…”
Section: Introductionmentioning
confidence: 99%